การศึกษาเปรียบเทียบการให้และการจัดการเกี่ยวกับสวัสดิการ และผลประโยชน์เกื้อกูลของบริษัทการค้าชั้นนำในกรุงเทพมหานคร - นพดล จรัสศรี (จุฬาลงกรณ์มหาวิทยาลัย, 1979)
The trading firm performs marketing functions for the community by bringing merchandises from the producers to customers. As much, the performance of the employees directly affects the degree of success of the company. Among the most effective means to retain good employees with the company are the provision of welfare and fringe benefits. Therefore this dissertation addresses itself to the study of the provision of welfare and fringe benefits of leading trading firms and how it would help the firms in achieving their objectives. A survey was made on leading trading firms in Bangkok with 4 objectives: 1. to compare what are provided with the legal requirements. 2. to compare such cost and their proportion to remuneration expenses and similar statistics of the other countries. 3. to rank the company’s expectation of return on welfare and fringe benefit provisions. 4. to build a model of welfare and fringe benefit programs practiced by the majority of the companies. This research finds that the leading trading firms in Bangkok provide welfare and fringe benefits for their employees to the extent more than the legal requirements. Many of the provisions are not legally required but are nevertheless provided: e.g., employee services, direct monetary benefits and pay for more leisure time. For the fiscal year 1978, the cost of the employee welfare and fringe benefits was estimated to be about Baht 11,787 per head or nearly Baht 1,000 per head per month. Proportionally, thee expenses was 19.0 per cent of total remuneration. These statistics are considerably lower than those of the United States of America in the fiscal year 1975 the latest figures available. With regard to ranking the order of expectation of the Management, it is found that the first objective is to utilize the labour force effectively and to be good labour relations, to be safeguard for and the progress of employee working life, to pay indirect wage and to be a mean of good public relations accordingly. A model of the provision of welfare and fringe benefits of leading trading firms is constructed based upon the information gathered in this dissertation.